Polyphasic characterization of Nocardioides aquaegermanicae sp. nov., a novel water-derived actinobacterium - Shuangqing Zhou; Sarah Kirstein; Lara Keunecke; Alexandra Lehmann; Lars-Olaf Schulz; Marlen Jando; Gabriele Pötter; Meina Neumann-Schaal; Yvonne Mast; Imen Nouioui (PLoS ONE, 2026)
Strain DSM 117947 T was isolated from a Micromonospora matsumotoense co-culture originating from a water sample collected in Germany. The strain was subjected to a polyphasic taxonomic analysis. It exhibited 99.3% 16S rRNA gene sequence similarity with Nocardioides aurantiacus DSM 12652 T . Digital DNA-DNA hybridization and average nucleotide identity values between the strain and its close phylogenetic neighbour were below the threshold of 70% and 95−96% for prokaryotic species demarcation, respectively. The strain had a polar lipid profile composed of diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), phosphatidylmethylethanolamine (PME), phosphatidylinositol (PI), glycophospholipid (GPL), and phospholipids (PLs). The predominant menaquinone (>20%) was MK-8(H 4 ). The major fatty acids (>5%) were C 16.0 , C 16:1 ω7c, and C 18:1 ω9c. The genomic G + C content of the strain is 73%. The chemotaxonomic, biochemical, enzymatic, and genomic features distinguished the strain from its close relative, and justify its assignment to a novel species, for which the name Nocardioides aquaegermanicae sp. nov., is proposed, with strain DSM 117947 T (WG_orange T = KCTC 59414 T ) as the type strain.